2008
DOI: 10.1021/cm703158f
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Organic−Inorganic Templating and Thermoelectric Properties of High-Aspect-Ratio Single-Crystal Lead Telluride Nanorods

Abstract: Chalcogenides such as bismuth telluride and lead telluride exhibit high thermoelectric figures of merit ZT 1-3 in the bulk because of a combination of high electrical conductivity σ and Seebeck coefficient S, and low thermal conductivity κ, making them attractive for refrigeration and generating electrical power from heat. 4-6 Nanostructuring these materials along one dimension (e.g., nanolayers) has been shown to increase ZT because of size and quantum effects on S, σ, and κ. 7,8 Greater degrees of confinemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…The method is superior in simplicity, rapidity, and high yield. Different from the previously reported single-crystalline PbTe nanowires and nanorods [19][20][21], the morphology analyses reveal that the nanorods with rough surfaces are composed of PbTe nanoparticles, whose sizes range from 30 to 50 nm. Such rough polycrystalline nanorods are promising for high-efficiency TE micro-devices.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The method is superior in simplicity, rapidity, and high yield. Different from the previously reported single-crystalline PbTe nanowires and nanorods [19][20][21], the morphology analyses reveal that the nanorods with rough surfaces are composed of PbTe nanoparticles, whose sizes range from 30 to 50 nm. Such rough polycrystalline nanorods are promising for high-efficiency TE micro-devices.…”
Section: Discussioncontrasting
confidence: 93%
“…Harman et al [8] have fabricated PbTe/PbSe quantum dot superlattices and estimated a ZT value of $2.0 at 300 K. The Seebeck coefficient enhancement in nanostructured PbTe was also found when the grain sizes were comparable with the average excitonic Bohr radius (about 46 nm) [12,13]. Many of the previous studies on nanostructured PbTe were mainly focused on the controlled synthesis of different morphologies, including PbTe nanoparticles [14,15], nanospheres [16], nanotube [16][17][18], nanowires [19,20], nanorods [21], nanoboxes [22], and hierarchical dendrites [23]. Among them, 1D PbTe nanostructures are very promising for highefficiency TE micro-devices.…”
Section: Introductionmentioning
confidence: 99%
“…Films of cross-linked Bi 2 S 3 nanorods have been fabricated on Si substrates and showed a high Seebeck coefficient of −755 µV/K [240]. High aspect ratio PbTe nanorods were assembled into thin films onto glass substrates prepatterned with Au electrodes by dip coating, and a subsequent hydrazine treatment was applied in order to enhance the film conductivity [241]. Such films showed a band gap of 0.27 eV, and a Seebeck coefficient of 263 µV/K, which is comparable to bulk PbTe.…”
Section: Thermoelectric Properties Of Elongated Nanoparticlesmentioning
confidence: 99%
“…Purkayastha et al 15 demonstrated a new two-step organic-inorganic templating route to synthesise high aspect ratio PbTe nanorods from Te nanotubes and pointed out that the aspect ratio of the nanorod could be tailored by changing reaction temperature and cetylether concentration. Wan et al 16 prepared PbTe nanorods via the composite hydroxide mediated.…”
Section: Introductionmentioning
confidence: 99%